Evaluating Reforms of Local Public and Social Services in Europe More Evidence for Better Results (Governance and Public Management,, 2018)
This book explains the increasing demand for evaluation as a result of the increasing frequency of reforms to local services, influenced by the New Public Management doctrine, the severe austerity policy in many European countries, and the wish to increase quality and reduce costs of public services, especially at the local (sub-national) level. Positioned at the interface of local services and evaluation research, it will enable the utilization of evaluation-generated knowledge in evidence-based policy making by focusing on the lessons learned from evaluation of local service delivery. It encompasses local public and social services (including waste, water, public transport, healthcare, education and eldercare) and examines the hypothesis that there is a North-West-South-East divide in Europe in terms of the evaluation of local service reforms. Particular attention is devoted to the explanatory function of evaluation. Providing fresh insight into the functioning of local government machinery in contemporary Europe, this book will appeal in particular to practitioners and students of local government, public economy, public administration and policy.